Association Between Plasma N-Acylethanolamides and High Hemoglobin Concentration in Southern Peruvian Highlanders - Alarcon-Yaquetto, DE (2017)
High-altitude (HA) hypoxia is a stressful condition endured by organisms through different mechanisms. Failing to adapt to chronic HA exposure leads to a disease called chronic mountain sickness (CMS) characterized by excessive erythrocytosis (hemoglobin [Hb] ≥19 g/dL for women and ≥21 g/dL for men). Genes encoding for peroxisome proliferator-activated receptor (PPAR) subunits α and γ have been proposed as candidate genes for HA adaptation. N-acylethanolamides (NAEs) are endogenous fatty acid substances that bind to PPAR-α and -γ. NAEs are also able to modulate the endocannabinoid system, a signaling pathway activated in physiological stressful conditions. In the frame of a metabolomic study, we measured plasma levels of four NAEs: palmitoylethanolamide (PEA), oleoylethanolamide (OEA), stearoyl ethanolamide (SEA), and linoleoyl ethanolamide (LEA) in natives from Puno (3830 m), a city located in the Peruvian Southern Andes, and Lima (150 m). All NAEs were significantly higher in the HA population (p < 0.001, q < 0.001). Subjects with higher NAE values were those with higher Hb concentration and lower pulse oxygen saturation. However, there was no association between NAEs and CMS score. Our results suggest that PEA and OEA could be involved in physiological regulation following long-term HA exposure.